Phosphorus-calcium metabolism in postmenopausal women with diabetes mellitus = Фосфорно-кальцієвий обмін у постменопаузальних жінок, хворих на цукровий діабет - Kyryliuk, M. L.; Atanova, Ya. O. (Journal of Education, Health and Sport, 2015)
Kyryliuk M. L., Atanova Ya. O. Phosphorus-calcium metabolism in postmenopausal women with diabetes mellitus = Фосфорно-кальцієвий обмін у постменопаузальних жінок, хворих на цукровий діабет. Journal of Education, Health and Sport. 2015;5(12):544-554. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.42478 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A544-554 http://pbn.nauka.gov.pl/works/686447 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. PHOSPHORUS-CALCIUM METABOLISM IN POSTMENOPAUSAL WOMEN WITH DIABETES MELLITUS ФОСФОРНО-КАЛЬЦІЄВИЙ ОБМІН У ПОСТМЕНОПАУЗАЛЬНИХ ЖІНОК, ХВОРИХ НА ЦУКРОВИЙ ДІАБЕТ 1Kyryliuk M. L., 2Atanova Ya. O. Кирилюк М. Л., Атанова Я. О. Український науково-практичний центр ендокринної хірургії, трансплантації ендокринних органів і тканин МОЗ України (Україна, 01021 Київ, Кловський узвіз 13А) 01021 Ukraine Kyiv, Klovskyi uzviz 13A Ukrainian Scientific and Practical Center of Endocrine surgery, Transplantation of Endocrine Organs and Tissues of Health of Ministry of Public Health of Ukraine, Kyiv www.endosurg.com.ua, online@endosurg.com.ua, kmlazar@ukr.net1, amo_te@bk.ru2 РЕЗЮМЕ Кирилюк М. Л., Атанова Я. О. ФОСФОРНО-КАЛЬЦІЄВИЙ ОБМІН У ПОСТМЕНОПАУЗАЛЬНИХ ЖІНОК, ХВОРИХ НА ЦУКРОВИЙ ДІАБЕТ В роботі досліджено стан фосфорно-кальцієвого обміну у постменопаузальних жінок, хворих на цукровий діабет, в залежності від типу цукрового діабету, стажу менопаузи, стажу діабету, маси тіла, типу цукрознижуючої терапії. Показано, що концентрація іонізованого кальцію в крові, загального кальцію та неорганічного фосфору не може слугувати головними маркерами стану мінеральної щільності кісткової тканини у постменопаузальних жінок, хворих на на цукровий діабет 2-го типу, за умов відсутності тяжкої хронічної ниркової недостатності та відповідної коморбідної патології. Виявлено, що препарати сульфонілсечовини та інсулінотерапія у сполученні із бігуанідами не впливають на показники фосфорно-кальцієвого обміну у постменопаузальних жінок із цукровим діабетом 2-го типу. Ключові слова: фосфорно-кальцієвий обмін, цукровий діабет, менопауза. RESUME Kyryliuk M. L., Atanova Ya. O. PHOSPHORUS-CALCIUM METABOLISM IN POSTMENOPAUSAL WOMEN WITH DIABETES MELLITUS In this work it was investigated the state of phosphorus-calcium metabolism in postmenopausal women with diabetes mellitus depending on the type of diabetes, length of menopause and diabetes, body weight, type of hypoglycemic therapy. It is shown that the concentration of ionized calcium, general calcium and inorganic phosphorus in the blood can not serve as the main marker of the state of bone mineral density in postmenopausal women with diabetes mellitus type 2 in in cases of absence of severe chronic renal failure and related comorbid pathology. It was found that sulfonylureas drugs and insulin in combination with biguanide not affect on performance of phosphorous-calcium metabolism in postmenopausal women with diabetes mellitus type 2. Keywords: phosphorus-calcium metabolism, diabetes mellitus, menopause. Kyryliuk Mykhailo - Prof, MD, PhD, DMSci, Head the Department of Neuroendocrinology and General Endocrinology http://lazarevich.at.ua/ Atanova Yana - MD, endocrinologist